The impact of halal knowledge and attitudes on purchase intention: insights from Sabah, Malaysia - Nurul Atiqa Mohd Tahir; Aizul Azri Azizan; Sharifudin Md. Shaarani; Noor Qhairul Izzreen Md Nor; Umi Hartina Mohamad Razali; Ahmad Riduan Bahauddin (Faculty of Food Science and Nutrition, UMS, 2025)
This study aims to assess the knowledge and attitudes of the Muslim community in Kota Kinabalu, Sabah, Malaysia, towards halal products and their influence on purchasing halal food products. A questionnaire was filled out by 390 respondents in total. The survey was administered both in person and online. Data were analyzed using descriptive statistics and Pearson correlation to evaluate relationships between knowledge, attitudes, and purchase intentions. Findings from this study revealed that the majority of respondents demonstrated an acceptable understanding and attitude toward halal principles and their application to food products. Knowledge and attitude towards halal also showed a significant positive correlation with the intention to buy halal food products (p<0.05). In conclusion, enhancing consumer knowledge and fostering positive attitudes are critical drivers of purchase intention for halal products. Continuous awareness campaigns and targeted promotions are essential for sustaining the growth of the halal industry by increasing awareness and promote halal products.